Die Suid-Afrikaanse kapelaansdiens en die beginsel van 'n regverdige oorlog: die Namibiese Vryheidsoorlog, 1966-1989 - Bredenkamp, Izette; Wessels, André (Faculty of Humanities, University of the Free State, 2010)
From 1966 to 1989, South Africa was involved in the Namibian War of Independence, also known as the Border War or the Bush War. In due course, chaplains of the South African Defence Force were also sent “up north”, or ministered to troops in bases in South Africa. In this article, the controversial issue of the so-called just war principle is discussed in the light of the reasons why the war broke out in South West Africa (Namibia). Interviews with several chaplains who ministered during the war were conducted in an effort to obtain the viewpoint of as many people (representing several religious denominations) as possible, in an effort to ascertain how chaplains viewed the Namibian War of Independence, and to determine the reaction their role elicited at the home front and abroad.
Keywords: Namibian War of Independence; Border War; Bush War; Caplains of the South African Defence Force